Arrangements for Archive Depreciation to Improve Regional Government Performance in Perspective Legislation in Indonesia: Pengaturan Penyusutan Arsip Guna Peningkatan Kinerja Pemerintah Daerah Dalam Perspektif Perundang- Undangan di Indonesia - Wulandari, Pebriana; Syamsir, Syamsir; Kosariza, Kosariza (Fakultas Hukum Universitas Jambi, 2024)
The aim of this research is to determine and analyze the arrangements for archival depreciation in order to improve the performance of local governments from a legislative perspective in Indonesia. This research uses normative juridical research methods. In this research, two research approaches were used, namely the statutory approach and the conceptual approach. The results of this research are Article 27 of Law Number 43 of 2009 concerning Archives and Article 12 of Government Regulation Number 28 of 2012 concerning Implementation of Law Number 43 of 2009 concerning Archives regulating procedures for depreciation of archives. However, there are differences between the two articles in terms of archive depreciation criteria. Article 27 of the Archives Law regulates that depreciation of archives is carried out based on the archive's use value. The use value of archives is the benefit obtained from archives for organizations or society. Meanwhile, Article 12 PP Archives regulates that archive depreciation is carried out based on the archive's use value and organizational needs. Organizational needs are the organization's need to use archives in carrying out its duties and functions. These differences in archive depreciation criteria can cause confusion and uncertainty for local governments in carrying out archive depreciation. Regional governments do not know which laws and regulations must be complied with in carrying out archive depreciation.